HyperCVAD for VAD-resistant multiple myeloma - Dimopoulos, M.A.; Weber, D.; Kantarjian, H.; Delasalle, K.B.; Alexanian, R. (American Journal of Hematology, 1996)
More effective and safer regimens are needed for patients who have advanced multiple myeloma resistant to or relapsing despite prior treatment with alkylating agents and VAD. We treated 58 such patients using the combination of twice daily cyclophosphamide (total dose 1.8 g/m2) and VAD (hyperCVAD). Treatment was given to outpatients followed by G-CSF at 5 μg/kg/d until granulocyte recovery. Twenty-three patients responded (40%), with a median duration of granulocyte depression to less than 500/μl of 4 days and a mortality rate of 2%. The median survival time for all patients was 15 months, and the median remission time of responding patients was 8 months. Patients who had low LDH, low B2M, or primary resistant disease lived significantly longer than patients without these features. The combination of fractionated cyclophosphamide and VAD provided an effective and safe rescue treatment for many patients who had advanced myeloma resistant to standard therapies.
Keywords: chemotherapy for myeloma; resistant multiple myeloma; VAD